MENINGKATKAN KEMAMPUAN GURU KELAS DALAM MENULIS SOAL PILIHAN GANDA MELALUI WORKSHOP DI SEKOLAH SD NEGERI 030 KENCANA KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Asridar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the workshop implementation of writing multiple-choice questions to improve the teachers’ ability at class IV-V. The research was conducted at SD Negeri 030 Kencana. The subject of the research involved 30 teachers at class IV-V. This classroom action research was conducted in three cycles. For each cycle, there were two meetings, except for cycle 3 only 1 meeting and each meeting was conducted in 6 hours. The research instrument was an action plan, action implementation, observation and evaluation, and reflection. The results of work observations in the workshop on writing multiple-choice questions obtained the data in cycle 1, which were A in 32.5%, B in 52.5%, and C in 15% in meeting 1. In cycle 1, meeting 2 was found A at 37.5%, B at 52.5%, and C at 30%. In cycle 2, meeting 1 indicated A at 37.5%, B at 55%, and C at 7.5%. In cycle 2, meeting 2 indicated A at 42.5%, B at 42.5%, and C at 15%. In cycle 3, it was found A at 32.5%, B at 62.5%, and C at 5%. The results showed that the teacher performance results had been able to achieve the indicators of the workshop on writing multiple-choice questions successfully by passing a percentage of 80% for scores A and B. Thus, the workshop activities were successful to improve the classroom teachers’ ability in writing multiple-choice questions.